THE ROLE OF THE HUMAN FACTOR IN IT PROJECT RISKS: A SYSTEMATIC APPROACH TO TEAM BUILDING - SKRYPNYK, TETIANA; VOZNYUK, LEONID (Herald of Khmelnytskyi National University. Technical sciences, 2025)
In today’s dynamic business environment, a significant number of companies that utilize a project-based approach are facing high risks related to project termination. In most cases, the main cause is the human factor, which leads to decreased quality of the final product, project delays, or even cancellation due to funding cuts. This issue is especially evident in the field of Information Technology (IT), where project-based work is an integral part of organizational operations. Forming an effective project team under the uncertainty inherent in IT projects is particularly challenging due to the lack of accurate information about the project scope at the planning stage. As a result, teams and their structures must be continuously adjusted, which increases the overall risk to the project’s success. This situation has led to a growing demand for highly qualified professionals who are not only technically skilled but also capable of adapting effectively to changing work conditions. A comprehensive and systematic approach to team formation becomes essential for the successful execution of IT projects. This involves defining functional roles, assessing competency levels, taking into account psychological characteristics of team members, and designing motivating workspaces. Neglecting this process often results in organizational inefficiencies, poor communication, and misalignment of responsibilities within the team — all of which contribute to the escalation of project risks. The relevance of this research lies in the need to improve methods of team selection for IT projects, especially under uncertain conditions. Properly selected and well-integrated teams can significantly reduce human-related risks and improve project performance across all stages of implementation.